Light energy dissipation in Quercus ilex resprouts after fire - Fleck, I.; Aranda, X.; El Omari, B.; Permanyer, J.; Abadia, A.; Hogan, K. P. (AUSTRALIAN JOURNAL OF PLANT PHYSIOLOGY, 2000)
Holm oak (Quercus ilex) plants that have resprouted after fire have higher photosynthetic capacity than control plants in intact vegetation. In this study, branches detached from forest plants were fed with dithiothreitol (DTT) in the laboratory to inhibit zeaxanthin production and thus reduce the dissipation of light energy as heat. This allowed us to test the hypothesis that plants with greater photosynthetic capacity, and therefore greater photochemical sink strength, would suffer a lower reduction in photochemical efficiency under stressful conditions. Greater rates of photochemistry in resprouts, which exhibited increased photosynthesis (A), leaf conductance (g), quantum yield of PSII (Delta F/F-m') and photochemical quenching (q(P)), were related to lower non-radiative dissipation of excess energy as indicated by 1 - (F-v'/F-m'). However, the fraction of energy remaining of that used in photochemistry or dissipated thermally in the PSII antennae was similar in resprouts and controls and was not affected by DTT, especially under high irradiance conditions. Zeaxanthin involvement in PSII protection operated in resprouts and controls since DTT induced the same kind of response (NPQ decrease) but was lower in resprouts. These chlorophyll fluorescence results suggest the participation of some additional mechanism for energy dissipation. Light capture characteristics of the photosynthetic apparatus did not differ between resprouts and controls, and leaf age did not play a determining role in the differences observed.
APSAPSThe following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: DTT; photochemical sink; Quercus ilex